Probiotics (Bacillus clausii and Lactobacillus fermentum NMCC-14) Ameliorate Stress Behavior in Mice by Increasing Monoamine Levels and mRNA Expression of Dopamine Receptors (D1 and D2) and Synaptophysin - Rehman, Mujeeb Ur; Ghazanfar, Shakira; Ul Haq, Rizwan; Ullah, Shakir; Khan, Salman; Wu, Jianbo; Ahmad, Waqar; Tipu, Muhammad Khalid (Frontiers in Pharmacology, 2022)
Stress is a physiological consequence of the body to adversity. Gut-brain axis and probiotics are gaining more interest to provide better treatment of stress and other neurological disorders. Probiotics (Lactobacillus fermentum NMCC-14 and Bacillus clausii, 1010 Colony Forming Unit (CFU)/day/animal, per oral) effects were investigated in acute (upto day 7) and subacute (days 8 to 14) restrain stressed and normal mice through behavioral paradigms (Elevated plus maze: EPM, Light dark box/Dark light box: LDB, and Open field test: OFT). Time spent in open arms of the EPM, light compartment of the LDB, and movable time, and time spent in the center of OFT, were significantly (p ≤ 0.05, n = 5) increased in probiotics treated restrain stressed mice. Enzyme-linked immunoassay (ELISA) determined blood cortisol and Adrenocorticotropic Hormone (ACTH) levels were reduced significantly (p < 0.05, n = 5) in probiotics treated restrained stressed mice. Hematoxylin and eosin (H&E) stained hippocampal slides also show less or no neurodegeneration in the probiotics treated animals. High-Performance Liquid Chromatography (HPLC) and Quantitative polymerase chain reaction (qPCR) were performed to determine monoamines level and mRNA expression of dopamine receptor subtypes (D1 and D2), and synaptophysin in mice's hippocampus (HC) and prefrontal cortex (PFC). Levels of dopamine, serotonin, and norepinephrine were also significantly (p < 0.05, n = 5) increased in HC and PFC in probiotics treated animals’ brains. Fold expression of mRNA of D1, D2 (except HC, LF-S, day 14) receptors, and synaptophysin were also significantly (p < 0.05, n = 5) increased in the same brain parts of probiotics treated stressed mice. Comparing LF and BC groups’ mice to the normal, only a significant (p < 0.05, n = 5) decrease was observed in serum ACTH and cortisol level on day 14 in Bacillus clausii treated mice, where all other parameters also showed improvement. Comparatively, Bacillus clausii showed more stress suppressant activity than Lactobacillus fermentum NMCC-14. However, both probiotic bacteria can be a better and safer therapeutic alternative for the ailment than the already available drugs.